On the Issue of Italian Borrowings, Their Absorption and Transformation in Spanish Secular Architecture of the Renaissance - Grigorieva, Elizaveta P. (Actual Problems of Theory and History of Art, 2016)
The article is devoted to the issue of Renaissance Spanish civil architecture development and to the problem of the influence of Italian samples. We attempted to cover the initial stage of dissemination of Renaissance aesthetics onto Iberian Peninsula. Renaissance aesthetics spread around the country by different means such as architecture sketches or completed plans made by Italian craftsmen; it was not perceived at once but through the prism of local traditions. In order to demonstrate the origin and development of the Renaissance style in Spanish civil architecture at the turn of the 16th century, some monuments has been given as an example: Manzanares el Real (late 15th century), La Calahorra (1509–1512), El palacio de los Duques del Infantado (1480 – early 16th century), la Casa de las Conchas (1493–1517). Much attention has been paid to the monuments created at the request of the Mendoza family, who were the first to borrow the Renaissance style. Spanish architects gradually went from just copying separate elements from the already thriving Renaissance to understanding the logic of Renaissance architecture. This transformation can be clearly seen in La Calahorra Castle.
Keywords: civil architecture; transformation Renaissance architecture; Spain; Renaissance; Mendoza; Spanish architecture